Basal-plane stacking-fault energies of Mg alloys: A first-principles study of metallic alloying effects. Issue 10 (October 2018) - Dong, Qing; Luo, Zhe; Zhu, Hong; Wang, Leyun; Ying, Tao; Jin, Zhaohui; Li, Dejiang; Ding, Wenjiang; Zeng, Xiaoqin
Abstract: Generalized stacking-fault energies (GSFEs) of basal-plane stacking faults I1 and I2 in Mg alloys have been studied based on first-principles calculations, where 43 alloying elements were considered. It is found that the most contributing features of alloying elements to GSFEs are bulk modulus, equilibrium volume, binding energy, atomic radius and ionization energy. Both bulk modulus and ionization energy exhibit positive relationships with GSFEs, and the others show opposite relationships. Multiple regressions have been performed to offer a quantitative prediction for basal-plane GSFEs in Mg- X systems. GSFEs, alloying effects of elements and the prediction model established within this work may provide guidelines for new Mg alloys design with better ductility.